Proton pump inhibitor responders who are not confirmed as GERD patients with impedance and pH monitoring: who are they?. Issue 1 (29th August 2013) - de, N.; Martinucci, I.; Savarino, E.; Bellini, M.; Bredenoord, A. J.; Franchi, R.; Bertani, L.; Furnari, M.; Savarino, V.; Blandizzi, C.; Marchi, S.
Abstract Background A short‐course of proton pump inhibitors (PPIs) is often used to confirm gastroesophageal reflux disease (GERD). However, some patients with PPI responsive heartburn do not seem to have evidence of GERD on impedance‐pH monitoring (MII‐pH). The aim of the study was to evaluate patients with reflux symptoms and a negative endoscopy, who well respond to PPIs with MII‐pH. Methods We enrolled 312 patients with GERD symptoms and negative endoscopy: 144 reported well‐controlled symptoms after 8‐week PPIs and 155 were non‐responders. Symptom relief was evaluated with GERD Impact Scale and visual analog scale score. All patients underwent MII‐pH off‐therapy. Thirteen patients were excluded from analysis. Patients were grouped as follows: non‐erosive reflux disease (NERD; increased acid exposure time, AET); hypersensitive esophagus (HE; normal AET, positive symptom association, SI/SAP); MII‐pH‐/PPI+ (normal AET, negative SI/SAP) in the responder group; MII‐pH‐/PPI‐ in non‐responders. Key Results MII‐pH in PPI responders (symptom relief during PPI therapy > 75%) showed: 79/144 NERD (54.9%); 37/144 HE (25.7%); 28/144 MII‐pH‐/PPI+ (19.4%). MII‐pH‐/PPI+ patients reported the same symptom relief when compared with NERD and HE. In non‐responder (symptom relief during PPI therapy < 50%) group, 27/155 patients were NERD (17.4%); 53/155 were HE (34.2%); 75/155 were MII‐pH‐/PPI‐ (48.4%). NERD diagnosis was significantly higher in responder group (p < 0.01). Conclusions & Inferences In a substantial subgroup of patients responding to PPI with typical reflux symptoms, the diagnosis of GERD cannot be confirmed with pH‐impedance monitoring. Proton pump inhibitor response and presence of typical symptoms are thus not reliable predictors of the diagnosis and antireflux surgery should always be preceded by reflux monitoring.